Babesia bovis infection alters the composition and assembly of Rhipicephalus microplus midgut microbiota - Corona-Guerrero, Iván; Maitre, Apolline; Abuin-Denis, Lianet; Morales-García, Rodrigo; Almazán, Consuelo; Obregón, Dasiel; Cabezas-Cruz, Alejandro; Mosqueda, Juan (Frontiers in Microbiology, 2025)
IntroductionBabesia bovis is one of the main causative agents of bovine babesiosis. Livestock farmers are constantly struggling to control the population of the tick vector and reduce babesiosis outbreaks. For this reason, the development of new control strategies is necessary. Tick microbiota consists of a diverse group of symbiotic, commensal, and pathogenic microorganisms. It has been shown that altering the microbiota population prevents the transmission of apicomplexan pathogens. This work represents a primary exploratory approach to determine the changes B. bovis infection causes in the microbiota of R. microplus.MethodsTwo calves were infested with R. microplus larvae; next, one of the calves was splenectomized and infected with Babesia bovis. Fifteen days after the infestation, engorged females were collected from each calf. Collected ticks were separated into two groups: 0 h and 72 h. Ticks from the 0 h group were dissected to extract their midgut the same day they were collected, while midgut dissection of the other group was done after 72 h of incubation. Thus, samples were separated into 4 experimental groups depending on their infection status and the time of the dissection. Total DNA was purified and the V4 region of the bacterial 16S rRNA gene was sequenced using Illumina MiSeq technology.ResultsData analysis showed fewer complex networks with reduced connectivity in infected ticks compared to the uninfected group. In both groups, the tick microbiota networks showed reduced node density at 72 h post-repletion. Different keystone taxa were found in all groups, indicating that midgut microbiota assembly is influenced by both tick developmental stage and the infection with B. bovis.DiscussionResults of this work aim to serve as a steppingstone in the development of anti-tick microbiota vaccines capable of impairing both the life cycle of R. microplus and B. bovis transmission.